RELATIONSHIP BETWEEN MOTHER'S KNOWLEDGE AND ATTITUDES ON THE PATTERN OF COMPLEMENTARY BREASTFEEDING WITH THE GROWTH AND DEVELOPMENT OF CHILDREN AGED 6-24 MONTHS IN THE WORK AREA OF THE BILATO HEALTH CENTER - arpin; nurlila s. mula; novian s. hadi (Jurnal Ilmiah dr. Aloei Saboe, 2022)
The growth and development of a child take place very quickly, including physical, social, emotional, and cognitive development. Gorontalo Province based on Riset Kesehatan Dasar (RISKESDAS) 2018 prevalence of nutritional status (BB/PB) at the age of 6-11 months very thin 8,60%, thin 15,05%, normal 69,51% and obese 6,84%, while in infants aged 11-23 months very thin 3,38%, thin 7,40%, Normal 86,69% and fat 2,53%. The study aims to determine the relationship between knowledge and attitudes of mothers about the pattern of giving complementary breastfeeding with the growth and development of children aged 6-24 months in the work area of ​​the Bilato Public Health Center. The method used in this research is quantitative research. The sampling technique used is a simple random sampling system, with a sample of 74 respondents, then analyzed using the Pearson Correlation statistical test. From the results of the statistical test, it was obtained with successive values of 0,007 < 0,05 0,018 < 0,05, 0,003 < 0,05 which means that there is a significant relationship between mother's knowledge about the pattern of complementary feeding with growth, mother's knowledge about the pattern of giving complimentary breastfeeding with development. Mother's attitude about the pattern of giving complimentary breastfeeding with growth and 0,060> 0,05 which means there is no relationship between mother's attitude about the pattern of giving complimentary breastfeeding with development. With the conclusion that there is a significant relationship between mother's knowledge about the pattern of giving complimentary breastfeeding and mother's attitude with growth, there is a relationship between mother's knowledge about the pattern of giving complementary feeding and there is no relationship between mother's attitude about the pattern of giving complimentary breastfeeding with development of children aged 6-24 months.